How friendly are the school-based assessment practices in Oyo State? A study in school effectiveness (2008)
There have always been complaints about students' performance in any set of assessments given to them. Some of the complaints given by the students why they do not perform well are always based on the fact that the assessment practices are not friendly. Therefore, this study was designed to evaluate how friendly the school based assessments practices were. All teachers and three primary five pupils in twelve schools were used. Therefore, a total of 346 teachers and 36 primay 5 pupils participated in the study. Two types of instruments were developed for the study, one was used to collect qualitative data and the other was used to collect quantitative data. There are some schools where teachers did not know whether or not school-based assessment time table exist or not. Some teachers believed that school-based assessment took place twice a term while some thought it is for three times in a term. Not many teachers inform their pupils when school-based assessment is scheduled to take place. In addition, the environment of taking test was friendly in some schools and not friendly in some schools. The implications of the findings are discussed.